Implementasi Program Pendidikan Karakter Baik dan Kuat (BAKU) - Muhammad Rizky Nurfauzan Samid (UNISBA Press, 2024)
Abstract. Daarut Tauhiid Islamic Boarding School is an institution known for its moral workshop. The flagship program owned by Pesantren Daarut Tauhiid is the BAKU (Good and Strong) character. One of the educational institutions owned by Daarut Tauhiid to implement the program is SMA Daarut Tauhiid Boarding School Putra Bandung. This research aims to: 1) Examine the policy background of the implementation of the BAKU character education program at SMA Daarut Tauhiid Boarding School Putra Bandung. 2) Identifying the steps of implementing the BAKU character education program for students at SMA Daarut Tauhiid Boarding School Putra Bandung. 3) Finding the results of the implementation of the BAKU character education program for students at Daarut Tauhiid Boarding School Putra Bandung High School. Researchers used descriptive qualitative methods as an effort by researchers to explore information related to the BAKU character education program through field observations, interviews, and also documentation as reinforcing evidence in the study. The results showed that: 1) The policy background of the implementation of the BAKU character education program at Daarut Tauhiid Boarding School Putra High School is to establish an Islamic educational institution by prioritizing Ma'rifatullah education and noble morals. 2) The implementation of the BAKU character education program for students at Daarut Tauhiid High School applies BAKU character indicators including Tawadhu, Honest, Sincere, Discipline, Resilient, Courageous. 3) The results of the implementation of the BAKU character education program for students at Daarut Tauhiid Boarding School Putra Bandung High School are marked by the assessment and rewards given to maintain the culture and existence of BAKU characters. Abstrak. Pesantren Daarut Tauhiid merupakan lembaga yang dikenal dengan bengkel akhlak. Program unggulan yang dimiliki oleh Pesantren Daarut Tauhiid adalah karakter BAKU (Baik dan Kuat). Salah satu lembaga pendidikan yang dimiliki oleh Daarut Tauhiid untuk menerapkan program tersebut yakni SMA Daarut Tauhiid Boarding School Putra Bandung. Penelitian ini bertujuan: 1) Mengkaji latar belakang kebijakan implementasi program pendidikan karakter BAKU di SMA Daarut Tauhiid Boarding School Putra Bandung. 2) Mengidentifikasi langkah-langkah pengimplementasian program pendidikan karakter BAKU pada siswa di SMA Daarut Tauhiid Boarding School Putra Bandung. 3) Menemukan hasil implementasi program pendidikan karakter BAKU pada siswa di SMA Daarut Tauhiid Boarding School Putra Bandung. Peneliti menggunakan metode kualitatif deskriptif sebagai upaya peneliti dalam menggali informasi terkait program pendidikan karakter BAKU melalui observasi lapangan, wawancara, dan juga dokumentasi sebagai penguat bukti dalam penelitian. Hasil penelitian menunjukan bahwa: 1) Latar belakang kebijakan implementasi program pendidikan karakter BAKU di SMA Daarut Tauhiid Boarding School Putra adalah untuk mendirikan lembaga pendidikan islam dengan mengutamakan pendidikan Ma’rifatullah dan akhlak mulia. 2) Implementasi program pendidikan karakter BAKU pada siswa di SMA Daarut Tauhiid menerapkan indikator karakter BAKU antara Tawadhu, Jujur, Ikhlas, Disiplin, Tangguh, Berani. 3) Hasil implementasi program pendidikan karakter BAKU pada siswa di SMA Daarut Tauhiid Boarding School Putra Bandung ditandai dengan adanya penilaian serta reward yang diberikan untuk menjaga budaya serta eksistensi karakter BAKU.